The sacrificial topic in Peruvian Sports Journalism’s Discourse. The case of the soccer player Paolo Guerrero - Pahuacho Portella, Alonso (2014)
This research explores the discursive construction of the quality of sacrifice of the soccer player Paolo Guerrero in printed Peruvian Sport Journalism during the Copa America Argentina 2011 and the World Cup Brazil 2014 Qualifiers. To do that, various strategies used in the newspaper articles are identified in order to represent the sacrifice as a supposed essence of our national identity. It argues that the exaltation of sacrificial worship through the figure of Guerrero constructs a “must-be” for the Peruvian nation, since this alleged sacrifice is always made for the nation and their entire community’s interests. The critical spirit of this work is to locate, within the journalistic texts referred, the fissures and paradoxes that are hidden in their own textures, so this essentialist ideology can be denature and propose a change of paradigm in this type of journalistic genre that is so popular in our country.